MgCl2 center dot 6C(6)H(11)OH: a high mileage porous support for ziegler-natta catalyst - Gnanakumar, Edwin S.; Thushara, K. S.; Gowda, Ravikumar R.; Raman, Sumesh K.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
A new and single phase molecular adduct of MgCl2 with six cyclohexanol molecules MgCl2 center dot 6C(6)H(11)OH (MgCyOH) has been synthesized. Structural insight to this adduct was obtained by a variety of physicochemical methods. C-13 CPMAS spectrum and single pulse MAS spectra with high power proton decoupling recorded at different relaxation time showed the presence of two different sets of magnetically unequal cylcohexanol molecules present around Mg2+. A Raman feature of MgCyOH at 712 cm(-1) confirms that cylcohexanol molecules are present around Mg2+ in an octahedral environment. MgCyOH has been used as support material to prepare Ziegler-Natta (Z-N) active catalyst. Textural property of above Z-N catalyst exhibits high surface area (236 m(2)/g) with high porosity. Above active catalyst has been screened for ethylene polymerization. Depending on the cocatalyst employed (Me3Al, Et3Al, and iso-Bu3Al) and ethylene pressure, polyethylene yield varies an order of magnitude, from 378 to 3570 g/g catalyst, indicating a possible creation of different active sites and different interaction between cocatalyst and catalyst.